Combined Differential scanning calorimetry, Raman and Brillouin spectroscopies: A multiscale approach for materials investigation - Veber, Alexander; Cicconi, Maria Rita; Reinfelder, Heike; de Ligny, Dominique (Analytica Chimica Acta, 2018)
A new experimental setup combining DSC, Raman and Brillouin spectroscopies was developed. In order to estimate its accuracy and stability a study of silicon and the alpha-beta quartz phase transition were performed. The data obtained demonstrated good agreement with previous studies using these three different techniques. For quartz, the temperature behavior of its 147 cm(-1) Raman mode was studied in detail. Using a two-phonon coupling treatment of the Raman band, we show for the first time that its behavior can be well described by Landau theory of first-order phase transitions. The combined DSC-Raman-Brillouin technique is a powerful tool for material science capable of studying thermal, structural and elastic properties simultaneously. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Raman spectroscopy; Brillouin spectroscopy; Calorimetry; Quartz; Phase transition